Network optoelectronic airspace monitoring system - Tevyashev , Andriy; Shostko, Igor; Zemlyany, Oleg (Transfer of innovative technologies, 2021)
The system is designed for circular or sector monitoring of airspace and allows you to automatically solve a wide range of problems of detection, recognition, identification of all observed highly maneuverable air objects and high-precision tracking of selected air objects (AO): aircraft, helicopters, UAVs, missiles, drones, quadcopters, artillery shells, mines, etc. with display and recording of their exact coordinates and visual images.